Assessing the efficiency of landscsape design in promoting biodiversity : a case study of the cultural heritage landscape in Papan, Perak / Andrea Angel Robert and Wan Noor Anira Wan Ali - Robert, Andrea Angel; Wan Ali, Wan Noor Anira (2024)
Biological diversity underpins ecosystem functioning and the provision of ecosystem services essential for human well-being. As the world faces increasing environmental challenges, preserving both natural and cultural heritage has become paramount. This research investigates the role of intentional landscape design in balancing conservation efforts with the preservation of cultural heritage in Papan Perak. Therefore, this paper focuses on the importance of the unique blend of ecological and cultural values present in Papan, Perak. The methods used are mixed with quantitative and qualitive by employing an online questionnaire methodology to gather data for the study.